Changes In Soft Tıssue Profıle Confıguratıon In Orthopedıc Treatment Of Skeletal Class 2 Cases: An Evaluatıon In The Natural Head Posıtıon - T. Ufuk Toygar Memikoğlu; Hakan Gögen; Murat Özbek; Ayşegül Köklü (Galenos Yayinevi, 1997)
The purpose of the study was to demonstrate the use of photographs taken in the natural head position (NHP) as a tool to evaluate the effects of functional appliances on clinical soft tissue profile configuration. It was further aimed to evaluate the interrelation between changes in hard and soft tissue structures. Our maternai consisted of photo graphs, lateral cephalometric and hand-wrist radiographs of 8 (5 girls and 3 boys) skeletal Class 2 children treated by activator. Material was collected at.preobservation, pretreatment, Angle Class I molar relationship and posttreatment periods. Repeated measure analyses and Duncan's tests were used to evaluate the changes in cephalometric and photographic parameters at different periods. Pearson's correlation coefficients were used to test the associations between hard and soft tissue changes during treatment. It was concluded that, use of photographs taken in the NHP may have significant advantages in the evaluation of soft tissue profile configuration. As expected, statistically significant changes were obtained both in cephalometric and photographice measurements during treatment. A correction of skeletal Class 2 discrepancy was observed together with a reduction in clinical soft tissue profile convexity and an improvement in labiomental curvature. However, these changes in hard and soft tissue structures were not found to be related to each other.